Towards an ecological feminist self beyond dualism and essentialism : an inquiry into the contributions made by cultural ecofeminism, critical-transformative ecofeminism and cyber-ecofeminism - Marincowitz, Friedl (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 1998.